2022
DOI: 10.1186/s13195-022-01019-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between Life’s Simple 7 and cerebrospinal fluid biomarkers of Alzheimer’s disease pathology in cognitively intact adults: the CABLE study

Abstract: Introduction This study sought to explore the association between Life’s Simple 7 (LS7) and cerebrospinal fluid (CSF) Alzheimer’s disease (AD) pathological biomarkers in the cognitively normal northern Chinese population. Methods From the Chinese Alzheimer’s Biomarker and LifestylE (CABLE) study, 1106 cognitively normal participants were enrolled. The mean age was 62.34 years, and 39.6% were female. LS7 scores were summed with each metric assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Another study discovered that mid-age Framingham Stroke Risk Profile was significantly associated with memory decline [37]. More studies have used LS7 to quantify CVH, and found that higher LS7 protect cognition [8,9,[38][39][40]. LE8 incorporating eight modifiable risk factors and uses a 100-point scale for assessment, providing a more comprehensive and nuanced perspective of CVH evaluation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Another study discovered that mid-age Framingham Stroke Risk Profile was significantly associated with memory decline [37]. More studies have used LS7 to quantify CVH, and found that higher LS7 protect cognition [8,9,[38][39][40]. LE8 incorporating eight modifiable risk factors and uses a 100-point scale for assessment, providing a more comprehensive and nuanced perspective of CVH evaluation [11].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy may be due to the difference of prediction models, measurement bias of Aβ42 and sample size. As a specific markers of AD, p-tau reflects intraneuronal tangles of hyperphosphorylated tau [ 36 , 37 ]. However, t-tau is a nonspecific marker of AD, and it reflects neuronal damage or intensity of degeneration [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor CVH has previously been related to greater white matter hyperintensity volume, silent brain infarcts, lower gray matter perfusion, and lower brain volume, which may mediate the association between CVH and cognitive function [29, 30]. In addition, a recent study showed that LS7 was related to levels of cerebrospinal Alzheimer's disease biomarkers, suggesting a link between better CVH and a lower degree of Alzheimer's disease pathology [31]. Furthermore, poor CVH may increase the risk of dementia by interacting with the β‐amyloid burden or promoting β‐amyloid and tau deposition, the pathological hallmarks of Alzheimer's disease [32–35].…”
Section: Discussionmentioning
confidence: 99%